Influence of weed-control measures on weed growth, yield and yield attributes of rainfed groundnut (Arachis hypogaea) - Rafey, A; Prasad, K (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during the rainy season of 1989-91 at Ranchi to study the effect of weed-control on weed growth, yield and yield attributes of rainfed groundnut (Arachis hypogaea L.). Pre-emergence application of pendimethalin (1.5 kg ai/ha) butachlor (1.5 kg ai/ha) and oxyfluorfen (0. 1 kg ai/hal was comparable with hand-weeding twice (15 and 25 days after sowing) in reducing weed density and its dry weight as well as in increasing pod yield/plant. Maximum dry-pod yield (1800 kg/ha) was obtained under hand-weeding twice and it was on a par with that under preÂ·emergence application ofÂ oxyfluorfen (1626 kg/ha). Among the chemical weed-control methods, pre-emergence application of oxyfluorfen had the least weed index (9.7%), followed by pendimethalin (1.5 kg ai/ha pre-emergence (11.6%). It was also found most economical, giving highest net profit (Rs 3764/ha), followed by hand-weeding twice (Rs 3 416/ha).